Implementation of an independent learning curriculum at Tunas Rimba 1 Purwokerto Kindergarten after the Covid-19 Pandemic - Isti Pujiati; Fauzi Fauzi (Edumaspul: Jurnal Pendidikan, 2023)
The Covid-19 pandemic requires the education curriculum in Indonesia to improve quality and development to the era's demands. Implementing the independent learning curriculum is one of the models for implementing the independent curriculum. The independent learning curriculum combines the independent curriculum and 2013 as a guide for student learning. The research examines the application of the independent learning curriculum at Tunas Rimba 1 Purwokerto Kindergarten. The method used is a descriptive qualitative research approach with data collection techniques through observation, documentation, and interviews. The research was conducted from January 1 to February 1, 2023, at Tunas Riba 1 Purwokerto Kindergarten, at Jl. Ksatrian No.60, Sokanegara village, East Purwokerto District, Banyumas Regency. Data analysis used a lesson study with three stages: planning, implementation, and reflection. The results of this study indicate that applying the independent learning curriculum at Tunas Rimba 1 Purwokerto Kindergarten starts from planning to reflection, as well as innovations before and after the implementation of the independent learning curriculum. It can be concluded that applying the independent learning curriculum impacts educational institutions, especially the learning system.